Economic and Energy Security of the Republic of Kazakhstan - Amirov, Azamat; Kozhukhova, Madina; Koshebaeva, Gaukhar; Biryukov, Valeryi; Zhiyenbayev, Miras (International Journal of Energy Economics and Policy, 2018)
The authors discuss the concept of energy and economic security of the Republic of Kazakhstan, arguing that energy security is a vital part of economic security of any country. Thus, energy security is to be strengthened in order to achieve better economic security. Kazakhstan has a large and pretty developed fuel and energy complex that certainly has a very significant impact on its economy. With the aim of analyzing Kazakhstan's energy security in the period of 2000-2015, we construct an energy security performance index that includes ten quantitative indicators operationalizing the four dimensions of energy security, namely the energy “availability”, “affordability”, “efficiency”, and “environmental stewardship”. The analysis clearly shows that Kazakhstan has been able to significantly increase its energy security performance over the 15 years. Due to the precise research design and data collected, the authors also provide insights into the behavior of each energy security dimension, demonstrating how Kazakhstan's energy security has been constantly changing in the period under analysis and identifying the strongest (“availability” and “affordability”) and weakest (“efficiency” and “environmental stewardship”) energy security dimensions. Keywords: Kazakhstan, Energy Security, Economic Security JEL Classifications: Q2, Q3, Q4 https://doi.org/10.32479/ijeep.6935